Assessment of Power Quality Performance Using Change Detection and DFT - K. Deepthi; Kusuma Gottapu; Eswararao Bireddi (Advanced Aspects of Engineering Research Vol. 11, 2021)
Uninterrupted investigation of Power Quality (PQ) issues in the electrical power distribution network has become a major issue for customers at various levels. Assessment of PQ disturbances is required for maintaining accurate output of electrical and electronic equipment. This paper presents a new technique for detecting and classifying PQ disturbances with minimal computational complexity. The occurrence of a disturbance in a sinusoidal signal is detected with the voltage slope detection system, and the type of disturbance is defined with the Discrete Fourier Transform (DFT). Results proves that the proposed method is optimum and the overall accuracy is high compared to other methods. It is observed that this method correctly detects and classifies the eleven types of PQ disturbances with higher accuracy, in the presence of noise environment also.